Structural Adjustment in the Transition : Case Studies from Albania, Azerbaijan, Kyrgyz Republic, and Moldova - Siegelbaum, Paul J. (Washington, DC: World Bank, 2013)
The study reviews the performance of four transition countries - Albania, Azerbaijan, the Kyrgyz Republic, and Moldova - in the areas of private, and financial sector development, identifying both their achievements, and challenges, to extract beneficial reform efforts, and alternative approaches, setting the pace for sustainable growth. These countries were selected because they are among the poorest in the region, whose problems are seemingly intractable, and have been largely detached from the international marketplace until the transition began. Thus, in terms of history, resource endowment, and proximity to markets they are viewed as "late reformers" in economic development, and competitiveness, despite policy reforms. Enterprise arrears, and soft budget constraints have been a significant problem in many transition economies, more often than not, manifested as some fiscal tightening occurred to offset budget constraints. Hence, a core challenge of the transition is to reduce the role of government from all encompassing presence, towards a professionally managed model, and one which provides high service delivery, strengthens civil institutions, and plays an effective regulatory role in a market economy. This requires improved financial discipline, reasonable fiscal policy, and structural adjustment, while privatization that promotes concentrated outsider ownership, and foreign participation, should be favored.